Synthesis of Zeolite A from Coal Fly Ash to Adsorb Heavy Metals - Soegiri Pringgomoeljo, Michael
The increasing demands of coal in Indonesia for power plants must be accompanied by the usage of coal combustion wastes. Coal fly ash as one of the power plant waste could be utilize for synthesize zeolite A. In this research, synthetic zeolite A from coal fly ash is modified for the usage of adsorbing heavy metals ion. The previous study has successfully synthesized zeolite A, with the biggest physical properties obtained by the following configuration: Natrium hydroxide/coal ratio of 1.4; Si/Al ratio of 0.75; and aging time of 8 hours. The replicated zeolite A was modified by using hydrochloric acid, ammonium nitrate, and ammonium hydroxide solution. The modification process was conducted in 80oC for 1 hours and followed by drying process in 120oC for 24 hours. After refluxing the zeolite with ammonium nitrate or ammonium hydroxide solution, drying process was followed by calcination in 550oC for 3 hours. The heavy metals adsorption test was conducted by using Lead, Zinc, and the mixture of both in the concentration of 200 mg/L. The effect of modifier solution concentration were studied by using 1 and 2 M solution. The modified zeolites were analyzed using XRD, SEM, isotherm adsorption, and AAS. The result showed that zeolite A could be replicated with the following properties: specific surface area of 28 m2/g, pore diameter of 5.48 nm, pore volume of 8.95×10-3 cc/g, and degree of crystallinity of 92.81%. Maximum adsorption of heavy metals ion was obtained by using zeolite A modified with 2 M ammonium nitrate solution. The result showed that 99.75% of lead ion and 99.92% of zinc ion could be adsorbed. Modification with hydrochloric acid led to dealumination of zeolite while ammonium nitrate and ammonium hydroxide solution performed ion exchange with zeolite. Desilication of zeolite by using ammonium hydroxide resulted in minor zeolite A crystal removal. The increasing concentration of modifier from 1 to 2 M did not significantly affect the physical properties of zeolite. From this study, It implied that two main factors contributed to heavy metals adsorption by using zeolite A were cubical structure of zeolite A and pore diameter.